2017
DOI: 10.1177/0030222816686609
|View full text |Cite
|
Sign up to set email alerts
|

“I thought they should know… that daddy is not completely gone”

Abstract: is Lecturer on the Practitioner Doctorate in Counselling Psychology at the University of Roehampton in the United Kingdom. Her research areas of interest concern anomalous experiences, bereavement, continuing bonds, post-traumatic growth, spiritual, existential and religious meaning-making and qualitative research methods. Adrian Coyle is Professor of Social Psychology at Kingston University in the UnitedKingdom. His areas of research expertise concern the psychology of religion, loss and bereavement, identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…For discussions and analyses of sensed presence experiences, see, for example, Castelnovo et al (2015), Ratcliffe (2021), Millar (2021), Rees (1971Rees ( , 1975 and Steffen and Coyle (2017). In noting that sensed presence experiences are typically non-veridical, we do not suggest that they are abnormal or pathological.…”
mentioning
confidence: 80%
“…For discussions and analyses of sensed presence experiences, see, for example, Castelnovo et al (2015), Ratcliffe (2021), Millar (2021), Rees (1971Rees ( , 1975 and Steffen and Coyle (2017). In noting that sensed presence experiences are typically non-veridical, we do not suggest that they are abnormal or pathological.…”
mentioning
confidence: 80%
“…The ways in which parents model their grieving behavior have been found to directly affect the way surviving children react to the death of their sibling (Morris et al, 2016). When bereaved parents choose not to disclose their feelings about the illness or death experience, it affects their ability to make sense of the death, which can have deleterious effects on surviving siblings' postloss functioning (Steffen & Coyle, 2017). Research suggests that family communication about death and illness has been shown to be a protective factor for surviving family members during bereavement.…”
Section: Research Evidence On Death Of a Childmentioning
confidence: 99%